Les droits de la femme dans la jurisprudence de la Cour Constitutionnelle égyptienne après les "Printemps Arabes" (Stato, Chiese e pluralismo confessionale, 2015)
Il contributo, sottoposto a valutazione, è destinato alla pubblicazione nel volume Il ruolo delle donne nelle società islamiche dopo le "Primavere arabe” tra tutela giurisdizionale e sistema politico in trasformazione, collana del Devolution Club “Nuovi studi di Diritto Pubblico Estero e Comparato”, Maggioli, Rimini, 2015.SOMMAIRE: 1. Préface - 2. Religion et État dans la ʺthéocratie constitutionnelleʺégyptienne – 3. La jurisprudence constitutionnelle entre l’article 2 et l’affirmation des droits des femmes – 4. La Cour constitutionnelle égyptienne en tant que garante de la primauté du droit et des principes de la charia. Abstract This work addresses the issue of women's rights in Islamic society. Particularly, attention is focused on a legal system, the Egyptian, who is heavily innervated by the principles of Islamic law. On the relationship between the principles of the Sharia and Women's Rights has repeatedly ruled the Constitutional Court that, with its peculiar interpretative reasoning on scriptural texts, has enabled the survival of the rules protecting women in the legal system of the State.